Contact to Natives Among Recent Turkish Migrants in Germany: Gender Differences and Potential Explanations - Seibel, Verena (Frontiers in Sociology, 2020)
Migrant men and women still differ extensively in their integration chances within receiving societies. Research suggests that next to educational discrepancies and traditional gender roles, migrant men benefit particularly from their contact to natives who facilitate the access to other relevant resources such as employment. However, we know actually very little about how recent migrant men and women build their social networks within receiving societies, how their networks differ, and why they potentially differ. In this paper I therefore study Turkish migrants in Germany within their first years after migration and the extent to which Turkish men and women differ in their likelihood to have contact to natives. Theoretically, I explore three main determinants for potential gender differences: Family influence, opportunity structure, and personal preferences. I thereby make use of the two-wave data from the ‘Social Cultural Integration Processes’ Project (SCIP) which studies migrants within their first three years after migration. I find that after three years after migration Turkish women are not only more likely to report to have no contact to natives than Turkish men; Even if they do have contact, this contact occurs significantly less frequent among Turkish women than among Turkish men. Results suggest that Turkish women, who migrated for family reasons are exposed to the influence of the family in the receiving country, which is often found to govern social behaviour. Also, compared to Turkish men, Turkish women are less likely to be employed which limits their opportunity to meet natives. Gendered preferences for contact to natives, however, do not explain why Turkish women have less contact to natives than Turkish men.